The Role of Adherence to Therapy and Healthy Lifestyle in Controlling Type 2 Diabetes in Indonesia: A Literature Review - Fitri, Salsabila Dwi; Ananta, Yorasakhi (Dinasti Accounting Review, 2025)
Type 2 Diabetes is one of the non-communicable diseases with high prevalence in Indonesia. One important approach in its management is compliance with medical therapy and the implementation of a healthy lifestyle. This article aims to examine the role of compliance with therapy and a healthy lifestyle in controlling Type 2 Diabetes through a systematic literature review approach. The method used is the Systematic Literature Review (SLR) by searching articles from databases such as Google Scholar and Mendeley. The results of the study indicate that compliance with therapy and a healthy lifestyle have a significant effect on lowering blood glucose levels and preventing long-term complications. This study also provides an important overview for policy planning and patient education. This article is expected to be the basis for further research and evidence-based interventions in the field of public health.